General Ludwik Michał Pac in Napoleon’s Service - Nawrot, Dariusz (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The article presents military service of Ludwik Pac under Napoleon’s banners. He was the last representative of a great old family deserving in history of Rzeczpospolita. He took part in the campaign of 1808 in Spain and he later fought in other war campaigns: Austrian, Russian, German and French ones, remaining at the same time faithful to emperor of the French, all the time. He was promoted to the rank of Major General and he showed skills of senior cavalry commander in the campaign of 1814. Despite his grand vanity, he knew how to estimate his qualifications and he knew how to use the advice of others in case of need. He was also respected and liked by others in the army.